İmam Şâfiî’nin (ö. 204/820) Hayatı ve Bazı Meziyetleri - Akdağ, Eyyup (Kastamonu Üniversitesi, 2020)
Imām Shāfiʿī ‘i is one of the most important and influential figures in the history of Islamic science. Imām Shāfiʿī ‘i, who is the founder of the Shafi‘i sect, is a member of the Qurayshi tribe. Due to the high level of his knowledge, he was deemed worthy of the mujaddid of the 2nd century Hijri. Imām Shāfiʿī ‘i, who started his education in science at an early age, became the most important name in science during his adolescence and started giving fatwa at the age of fifteen. Imām Shāfiʿī ‘i, with his opinions and thoughts, won the favor of a large Muslim community. It is observed that views, thoughts, and approaches in Islamic sciences such as fiqh, hadith, kalam and literature are brought to the fore and they were the subject in the studies conducted about him. In this study, the virtues and sensitivities of Imām Shāfiʿī ‘i in three areas, namely worshiping, shooting, and medicine is discussed. Additionally, in this research, the life of Imām Shāfiʿī ‘i is expressed in general terms.

İmam Şâfiî, İslâm ilim tarihinin önemli ve en etkili şahsiyetlerinden birisidir. Kendisine nisbet edilen Şâfi‘î mezhebinin kurucusu olan İmam Şâfiî, Kureyş kabilesine mensuptur. İlminin yüksekliğinden dolayı, Hicrî ikinci asrın müceddidliğine layık görülmüştür. Erken yaşta ilim tahsiline başlayan İmam Şâfiî, gençlik yıllarında ilimde zirve isim olmuş ve on beş yaşında fetva vermeye başlamıştır. İmâm Şâfi’î, görüş ve düşünceleriyle büyük bir Müslüman topluluğunun teveccühünü kazanmıştır. Onun hakkında yapılan çalışmalarda, daha ziyade fıkıh, hadis, kelâm ve edebiyat gibi İslamî ilim dallarındaki görüş, düşünce ve yaklaşımları ön plana çıkarılarak konu edinildiği görülmektedir. Bu çalışmada ise bu alanların dışında İmam Şâfiî’nin ibadet, atıcılık ve tıp olmak üzere üç alandaki meziyet ve hassasiyetleri konu edinildiği gibi ayrıca hayatı da genel hatlarıyla ifade edilecektir.
Keywords: Tasavvuf; İmam; Şâfiî; İbadet; Atıcılık; Tıp; Din Araştırmaları; Ṣūfism; Imām; Shāfiʿī; Worship; Shooting; Medicine; Religious Studies; 3. Good health